The Spoils of War “Divided into Three Parts”: A Comparison between Two Accounts in Skylitzes’ Synopsis historiarum and Kritoboulos’ History of Mehmed the Conqueror - Hristov, Yanko; Kitanov, Valentin (Studia Ceranea, 2020)
One can say without hesitation that during the highly dynamic medieval epoch rivalries and military clashes were of paramount importance in the struggles for dominance over the Balkan Peninsula. During the entire period, war-time activities included the capturing of those who had the misfortune to fall into the hands of the enemy. Various groups of soldiers and civilians alike have repeatedly tested the bitterness of captivity. Attempts to trace the fate of war-captives are, for understandable reasons, directly dependent on the data in the written records. The comparison of the various historical accounts is rather typical, even if the records deal with events that are different in time, place and participants. The present paper also compares two descriptions. This study encompasses two well-known historical accounts: the first one is from the chronicle (Synopsis historiarum) of John Skylitzes, while the second one is excerpted from Kritoboulos’ History of Mehmed the Conqueror. Despite all distinctions, there are some particular similarities. Both fragments concern the division of the spoils of war and the fate of the captured population and provide additional knowledge of the practices relating to prisoners of war in the Balkan medieval past.